Interest in expanded carrier screening among individuals and couples in the general population: systematic review of the literature. (25th February 2020) - Van Steijvoort, Eva; Chokoshvili, Davit; W Cannon, Jeffrey; Peeters, Hilde; Peeraer, Karen; Matthijs, Gert; Borry, Pascal
Abstract: BACKGROUND: Through carrier screening, prospective parents can acquire information about whether they have an increased risk of conceiving a child affected with an autosomal recessive or X-linked condition. Within the last decade, advances in genomic technologies have facilitated a shift from condition-directed carrier screening to expanded carrier screening (ECS). Following the introduction of ECS, several studies have been performed to gauge the interest in this new technology among individuals and couples in the general population. OBJECTIVE AND RATIONALE: The aim of this systematic review was to synthesize evidence from empirical studies that assess the interest in ECS among individuals and couples in the general population. As the availability and accessibility of ECS grow, more couples who are a priori not at risk based on their personal or family history will be presented with the choice to accept or decline such an offer. Their attitudes and beliefs, as well as the perceived usefulness of this screening modality, will likely determine whether ECS is to become a widespread reproductive genetic test. SEARCH METHODS: Four databases (Pubmed, Web of Science, CINAHL, Cochrane Library) were systematically searched to identify English language studies performed between January 2009 and January 2019 using the following search terms: carrier screening, carrier testing, attitudes, intention, interest, views, opinions, perspectives and uptake. Studies were eligible for inclusion if they reported on intentions to undergo a (hypothetical) ECS test, uptake of an actual ECS offer or both. Two researchers performed a multistep selection process independently for validation purposes. OUTCOMES: Twelve empirical studies performed between 2015 and 2019 were included for analysis. The studies originated from the USA ( n  = 6), the Netherlands ( n  = 3), Belgium ( n  = 1), Sweden ( n  = 1) and Australia ( n  = 1). The sample size of the studies varied from 80 to 1669. In the included studies, 32%–76% of respondents were interested in a (hypothetical) ECS test, while uptake rates for actual ECS offers ranged from 8% to 50%. The highest overall uptake was observed when ECS was offered to pregnant women (50%). By contrast, studies focusing on the preconception population reported lower overall uptake rates (8–34%) with the exception of one study where women were counseled preconception in preparation for IVF (68.7%). WIDER IMPLICATIONS: Our findings suggest that there may be discrepancies between prospective parents' reported intentions to undergo ECS and their actual uptake, particularly during the preconception period. As ECS is a new and relatively unknown test for most future parents, the awareness and comprehension within the general population could be rather limited. Adequate pre- and post-test counseling services should be made available to couples offered ECS to ensure informed reproductive decision-making, together with guidelines for primary health care professionals. Due to restricted nature of the samples and methods of the underlying primary studies, some of the reported results might not be transferable to a broader population. More research is needed to see if the observed trends also apply to a broader and more diverse population.